EFFECT OF ORAL ADMINISTRATION OF PHERETIMA ASPERGILLUM (EARTHWORM) IN RATS WITH CEREBRAL INFARCTION INDUCED BY MIDDLE-CEREBRAL ARTERY OCCLUSION. - Liu, Chung-Hsiang; Lin, Yi-Wen; Tang, Nou-Ying; Liu, Hsu-Jan; Huang, Chih-Yang; Hsieh, Ching-Liang (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
We investigated the curative effect of Pheretima aspergillum (earthworm, PA) on rats with middle cerebral artery occlusion (MCAo). The MCAo-induced cerebral infarction was established and its underlying mechanisms by counting the infarction areas and evaluating the rats’ neurological status. Immunostaining was used to test the expression of NeuN, and glial fibrillary acidic (GFAP), S100B, and brain-derived neurotrophic factor (BDNF) proteins. Our results showed that oral administration of PA for two weeks to rats with MCAo successfully reduced cerebral infarction areas in the cortex and striatum, and also reduced scores of neurological deficit. The PA-treated MCAo rats showed greatly decreased neuronal death, glial proliferation, and S100B proteins in the penumbra area of the cortex and in the ischemic core area of the cortex, but BDNF did not changed. These results demonstrated novel and detailed cellular mechanisms underlying the neuroprotective effects of PA in MCAo rats.